Evangelicalism and Old Testament Messianic Prophecy - Walter Creighton Marlowe (Religions)
A major plank in the Evangelical apologetics platform (especially for the Jewish witness) has always been the predictive prophecy about Jesus in the Hebrew Bible. The number of these prophecies or “predictions” varies widely among Conservative–Evangelical sources. A brief survey of claims about the number of Christ-related Old Testament (OT) prophecies ranges from 50–400+. Regardless, the assertion of direct, intentional Old Testament prophetic pronouncement about Jesus has been a non-negotiable mainstay of Evangelical thought and theology since its beginning. However, today, those who align with the Evangelical movement in general, would disagree on technical grounds with the traditional way that Messianic prophecy has been explained hermeneutically or exegetically. Progressive Evangelicals, however, generally are concerned with the interpretation or exegesis of biblical passages in their grammatical–historical–cultural contexts. The focus is on texts rather than traditions. An irony is that traditional and untraditional Evangelicals who favor contextual exegesis in principle are still very divided when it comes to explaining how the NT used the OT, especially in relation to Messianic prophetic texts. This article describes the problem and illustrates it with examples of how some older and newer Evangelicals disagree when commenting on OT Messianic prophetic passages.